Hunting alters seedling functional trait composition in a Neotropical forest. Issue 7 (1st July 2015) - Kurten, Erin L.; Wright, S. Joseph; Carson, Walter P.
Abstract : Defaunation alters trophic interactions between plants and vertebrates, which may disrupt trophic cascades, thereby favoring a subset of plant species and reducing diversity. If particular functional traits characterize the favored plant species, then defaunation may alter community‐wide patterns of functional trait composition. Changes in plant functional traits occurring with defaunation may help identify the species interactions affected by defaunation and the potential for other cascading effects of defaunation. We tested the hypotheses that defaunation would (1) disrupt seed dispersal, thereby favoring species whose dispersal agents are not affected (e.g., small birds, bats, and abiotic agents), (2) reduce seed predation, thereby favoring larger‐seeded species, and (3) reduce herbivory, thereby favoring species with lower leaf mass per area (LMA), leaf toughness, and wood density. We examined how these six traits responded to vertebrate defaunation caused by hunters or by experimental exclosures among more than 30 000 woody seedlings in a lowland tropical moist forest. Exclosures reduced terrestrial frugivores, granivores, and herbivores, while hunters also reduced volant and arboreal frugivores and granivores. The comparison of exclosures and hunting allowed us to parse the impacts of arboreal and volant species (reduced by hunters only) and terrestrial species (reduced by both hunters and exclosures). The loss of terrestrial vertebrates alone had limited effects on plant trait composition. The additional loss of volant and arboreal vertebrates caused significant shifts in plant species composition towards communities with more species dispersed abiotically, including lianas and low wood‐density tree species, and fewer species dispersed by large vertebrates. In contrast to previous studies, community seed mass did not decline significantly in hunted sites. Our exclosure results suggest this is because reducing seed predators disproportionately benefits large‐seeded species, partially compensating for the reduction of seed dispersers at hunted sites. Our results demonstrate that decreased seed dispersal and seed predation are important determinants of seedling community compositional change as a consequence of defaunation. Defaunation may also negatively impact carbon storage in tropical forests, by favoring lianas and low wood density tree species.